Analysis of New Medical Faculty Students' Knowledge Regarding Disasters and Analysis of their Wrong Answers to Disaster Questions - Dakwan Soaloon Harahap; Rayhan Hafiz Saragih (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2024)
This research aims to test and evaluate the knowledge of new students at the Faculty of Medicine at Malikussaleh University regarding disasters by analyzing incorrect answers to quiz questions. Quantitative research methods were used in this research. Data collection was carried out through distributing questionnaires using Google Forms. The sample size was 13.28% of the total students. It is known that the knowledge of students at the Faculty of Medicine, Malikussaleh University regarding disasters is good with avarage score is 86,32. However, the percentage of students who answered incorrectly was quite large on questions that included "basic disaster questions".